Dietary intervention for children and adolescents with familial hypercholesterolaemia - Maria Elena Capra; Giacomo Biasucci; Elisa Crivellaro; Giuseppe Banderali; Cristina Pederiva (BMC, 2023)
Abstract Familial hypercholesterolaemia (FH) is a frequent genetic disorder characterised by high plasma levels of total and LDL-cholesterol and premature atherosclerosis. If left untreated, affected subjects have a high risk of cardiovascular disease, as they are exposed to very high levels of LDL-cholesterol from birth. Healthy dietary habits and lifestyle are the first treatment option and, if started from childhood, represent a milestone in the prevention of atherosclerotic disease, both as a starting point and in combination with drug therapy. In this work, based on the main consensus documents available so far, we have evaluated the most up-to-date indications of the dietetic-nutritional intervention for the treatment of FH, delving into the peculiar aspects of the diet of the child/adolescent affected by FH. After an analysis of the macro- and micronutrients and the most common dietary patterns currently recommended, we highlighted some practical aspects, some frequent errors and some risks we could fall into when dealing with paediatric nutritional treatment. In conclusion, the dietary intervention for the child/adolescent with FH is a complex task, that should be individualised and tailored taking into account, first of all, the nutritional adequacy for growth and development, but also the multiple aspects linked to the child/adolescent's age, tastes and preferences, the family they belong to, the socio-economic context and the Country they live in.